Using qualitative exit interviews to explore schizophrenia burden and treatment experience in clinical trial patients - Simmons, Adam; O’Sullivan, Amy K.; Carpenter-Conlin, Julia; Carty, Michelle K.; Saucier, Cory; McDonnell, David (Frontiers in Psychiatry, 2024)
Evaluation of the efficacy and safety of investigational pharmacologic treatments for schizophrenia generally involves the use of well-known and validated quantitative measurement scales and clinician assessments. In 2022, the US Food and Drug Administration provided a final guidance to drug developers encouraging the collection of patient experience data related to the burden of disease and burden of treatment. In that guidance, the use of qualitative research methods was recommended as one way in which these data may be obtained. This report describes a novel approach to the integration of qualitative research into an open-label phase 3 clinical trial. In addition, patient perspectives of the symptoms of schizophrenia and their impact, coping mechanisms used to deal with the illness, past treatment experiences, unmet treatment needs, and patient perspectives about the experience of treatment with a study medication that was in development (at the time of the interview) were obtained using the patient's own voice.